2016
DOI: 10.1590/1678-4685-gmb-2015-0206
|View full text |Cite
|
Sign up to set email alerts
|

The association of very low-density lipoprotein receptor (VLDLR) haplotypes with egg production indicates VLDLR is a candidate gene for modulating egg production

Abstract: The very low-density lipoprotein receptor (VLDLR) transports egg yolk precursors into oocytes. However, our knowledge of the distribution patterns of VLDLR variants among breeds and their relationship to egg production is still incomplete. In this study, eight single nucleotide polymorphisms (SNPs) that account for 87% of all VLDLR variants were genotyped in Nick Chick (NC, n=91), Lohmann Brown (LohB, n=50) and Lueyang (LY, n=381) chickens, the latter being an Chinese indigenous breed. Egg production by NC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…LBC is a native breed from Lueyang city, Shannxi Province of China. Because of absence of selection for egg production, annual total number of eggs laid by LBC ranges from 150 to 230, peak production rate is 61%, and age at the first egg is 25 wk old ( Wang et al, 2016 ). Majority of LBC lay light-brown and brown eggs.…”
Section: Methodsmentioning
confidence: 99%
“…LBC is a native breed from Lueyang city, Shannxi Province of China. Because of absence of selection for egg production, annual total number of eggs laid by LBC ranges from 150 to 230, peak production rate is 61%, and age at the first egg is 25 wk old ( Wang et al, 2016 ). Majority of LBC lay light-brown and brown eggs.…”
Section: Methodsmentioning
confidence: 99%
“…As LBC was not subjected to selection for production traits, it shows large variations in egg production and growth traits, implying that some QTL could not possibly be fixed in this population ( Dang et al, 2020 ). In addition, our previous studies found that this breed sustained low genomic linkage disequilibrium ( Wang et al, 2016 ). These genetic features make it being a suitable population for fine mapping of some functional variants.…”
Section: Methodsmentioning
confidence: 79%
“…Recently, the potential role of expressions of insulin-like growth factor-1 ( IGF-1 ), prolactin receptor ( PRLR ), FSH , very low-density lipoprotein receptor ( VLDLR ), low-density lipoprotein receptor-related protein ( LRP ), estrogen receptor 1 ( ESR1 ), luteinizing hormone receptor ( LHR ), and estrogen receptor 2 ( ESR2 ) with egg traits have received serious attention ( Yao et al, 2010 ; Wang et al, 2016 ; Asiamah Amponsah et al, 2019 ; Cui et al, 2019 ; Asiamah et al, 2022 ).…”
Section: Studies On Expression Profile and Single Nucleotide Polymorp...mentioning
confidence: 99%